Numerical investigation of dynamic melting process in a thermal energy storage system using U-tube heat exchanger - Teng Xiong; Yong Wang; Xun Yang (Advances in Mechanical Engineering, 2017)
A thermal energy storage system using U-tube heat exchanger is proposed and compared with the system using single-tube heat exchanger. Based on the enthalpy-porosity method, three-dimensional numerical models using computational fluid dynamics approach are developed to simulate the dynamic melting of phase change material in the two systems. Variable specific heat technique and combined conduction–convection heat transfer models are applied to achieve precise simulation. The model is first validated using published data, and then, the heat flux across the tube is used to evaluate the heat transfer performance of the two systems. Moreover, parametric studies are performed to analyze the effect of heat transfer fluid flow rate on the U-tube system by six different cases. The results show that during the melting of phase change material, vertical temperature stratification occurs in both systems as a result of the intensified natural convection. The results also demonstrate that the U-tube system has better heat transfer performance than the single-tube system which has the same heat transfer area and boundary conditions, reducing the total charging time by 25%. Increasing the heat transfer fluid flow rate greatly enhances the heat transfer performance for the U-tube system, but further enhancement is limited by the fixed heat transfer area. This study provides an effective method to investigate the thermal behavior of thermal energy storage using phase change materials, and the results can be helpful in optimizing the future thermal energy storage design and practical applications.